2021
DOI: 10.21203/rs.3.rs-996346/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multiple distinct domains of human XIST are required to coordinate gene silencing and subsequent heterochromatin formation

Abstract: Background Mammalian dosage compensation is achieved by the inactivation of one X chromosome in XX individuals. In eutheria this process is initiated early in development by the long non-coding RNA XIST. Studies of the initiation of silencing by XIST have focussed on mouse models, so the domains of XIST required to induce silencing in humans, and their relationship with domains required to establish heterochromatin remain to be determined. Methods We have previously established an inducible XIST cDNA in soma… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Induction of an XIST cDNA integrated into an FRT site on chromosome 8p results in both silencing of flanking 8p genes and recruitment of heterochromatin marks 43 . Assessment of deletions spanning this full XIST reinforced that the 5’ end of XIST including the conserved A repeats was critical for silencing 44 . While the 5’ A repeats are essential for silencing, they are only sufficient to induce local silencing 45 .…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Induction of an XIST cDNA integrated into an FRT site on chromosome 8p results in both silencing of flanking 8p genes and recruitment of heterochromatin marks 43 . Assessment of deletions spanning this full XIST reinforced that the 5’ end of XIST including the conserved A repeats was critical for silencing 44 . While the 5’ A repeats are essential for silencing, they are only sufficient to induce local silencing 45 .…”
Section: Resultsmentioning
confidence: 96%
“…Thus, based on the current knowledge about the different functions of each XIST domain, we tried to generate a smaller construct that could recapitulate all the XIST functions. Domain A is crucial for silencing by recruiting proteins at the initiation of XCI in both, mice and humans 5,6,15,44 , and domain E is relevant for XIST/Xist localization also through protein interactions 12,28,29,48 . While A and E domains are clearly critical, our recent results suggested that the functional pathways utilized in human somatic cells may differ from those described in mouse differentiation (reviewed in 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…and what protein partners may be bound to them (Wutz et al 2002;Colognori et al 2019;Lee et al 2019b;Colognori et al 2020;Dixon-McDougall and Brown 2022). RepA was an obvious target because multiple studies have confirmed a requirement for initiating XCI silencing, and biochemical and cellular studies have identified a large suite of interacting protein partners, including PRC2 and SPEN (Zhao et al 2008;McHugh et al 2015;Monfort et al 2015).…”
Section: Mutational Analyses Have Determined How Each Domain Contribu...mentioning
confidence: 99%